Risks of concealing environmental degradation - Matt W. Hayward; Kaya Klop‐Toker; Salim Momtaz; Eliza Payne; Louisa Rebec; Robert J. Scanlon; Craig M. Shuttleworth; Nick Valentine; Andrea S. Griffin (Conservation Biology, 2026)
Current practice seeks to conceal the visual impact of land‐use change (i.e., development). Six percent of development impact assessments in Australia and 14% of the World Bank's assessments recommend visual impact mitigation. This mitigation results in, for example, vegetated buffer strips alongside cleared agricultural areas and earthen mounds that block environmental degradation from view. These measures make living alongside such development more palatable, but they conceal its negative effects from the general public. The scale of the problem is global with evidence of mandated regulatory drivers for concealment from around the world. These mitigation measures limit the emotional impact of development on people, reducing their likelihood of implementing pro‐environmental actions. It is important for the populace to see the scale of human impacts on the environment to increase the likelihood of pro‐environmental behaviors and decisions that will help ease the crises facing the environment. We recommend overtly exposing the public to environmental degradation to improve understanding of environmental impacts, increase environmental knowledge, trigger pro‐environmental emotions and actions, and help recalibrate people's understanding of biodiversity loss. Policies and research into the effect of creative public imagery designed to improve communication into environmental destruction while minimizing habituation are important, and ensuring that the “greening” of gray infrastructure yields genuine biodiversity benefits is also critical.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Nucleation feedback can drive establishment and maintenance of biased microtubule polarity in neurites - Hannah G. Scanlon; Gibarni Mahata; Anna C. Nelson; Scott A. McKinley; Melissa M. Rolls; Maria-Veronica Ciocanel (Mathematical Biosciences, 2025)

Divergent water use efficiency trends among eastern North American temperate tree species - Jacob D. Malcomb; Howard E. Epstein; Matthew A. Vadeboncoeur; Daniel L. Druckenbrod; Matthew Lanning; Lixin Wang; Heidi Asbjornsen; Todd M. Scanlon (Oecologia, 2025)
Both theory and observations suggest that tree intrinsic water use efficiency (iWUE)—the ratio of photosynthetic carbon assimilation to stomatal conductance to water—increases with atmospheric CO 2 . However, the strength of this relationship varies across sites and species, prompting questions about additional physiological constraints and environmental controls on iWUE. In this study, we analyzed tree core carbon isotope ratios to examine trends in, and drivers of, iWUE in 12 tree species common to the temperate forests of eastern North America, where forests have experienced changes in CO 2 , climate, and atmospheric pollution in recent decades. Across all site-species combinations, we found that tree iWUE increased 22.3% between 1950 and 2011, coinciding with a 25.2% increase in atmospheric CO 2 . iWUE trajectories varied markedly among tree functional groups and within species across sites. Needleleaf evergreen iWUE increased until circa 2002 before declining in recent years, while iWUE of broadleaf deciduous species continued to increase. The analysis of environmental controls on iWUE trends revealed smaller increases in iWUE in trees subjected to higher atmospheric pollution loads. Our results suggest that tree functional characteristics and atmospheric pollution history influence tree response to atmospheric CO 2 , with implications for forest carbon and water balance in temperate regions.

Proteoglycan-4 (PRG4) serum concentration is lower in aged mice, and genetic deficiency impacts survival probability, blood parameters, and bone during aging - Adam P. Tanguay; Nikhil G. Menon; Emma Slavin; Mikayla Moody; Erin McEwen; Gregory D. Jay; Joseph Lorenzo; Jenna M. Bartley; Vanessa M. Scanlon; Alix C. Deymier; Tannin A. Schmidt (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Impact of atmospheric dryness on solar-induced chlorophyll fluorescence: Tower-based observations at a temperate forest - Koong Yi; Rong Li; Todd M. Scanlon; Manuel T. Lerdau; Joseph A. Berry; Xi Yang (Remote Sensing of Environment, 2024)

Molecular characterization of dissolved organic matter in urban stormwater pond and municipal wastewater discharges transformed by the Florida red tide dinoflagellate Karenia brevis - Amanda Muni-Morgan; Mary G. Lusk; Cynthia Heil; Audrey H. Goeckner; Huan Chen; Amy M. McKenna; Patricia Scanlon Holland (Science of The Total Environment, 2023)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Distribution of rare earth and other critical elements in lignites from the Eocene Jackson Group, Texas - James C. Hower; Peter D. Warwick; Bridget R. Scanlon; Robert C. Reedy; Tristan M. Childress (International Journal of Coal Geology, 2023)

Seasonal weight loss effect in the hepatic fatty acid composition in Australian Merino, Damara and Dorper sheep - Mariana Palma; Tanya Kilminster; Timothy Scanlon; Chris Oldham; Johan Greeff; Manolis Matzapetakis; André M. de Almeida (Small Ruminant Research, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Sixty years of global progress in managed aquifer recharge - P. Dillon; P. Stuyfzand; T. Grischek; M. Lluria; R. D. G. Pyne; R. C. Jain; J. Bear; J. Schwarz; W. Wang; E. Fernandez; C. Stefan; M. Pettenati; et al. (Hydrogeology Journal, 2019)

Climate seasonality as an essential predictor of global fire activity - Michael V. Saha; Todd M. Scanlon; Paolo D'Odorico (Global Ecology and Biogeography, 2019)
Aim Fire is a globally important disturbance that affects nearly all vegetated biomes. Previous regional studies have suggested that the predictable seasonal pattern of a climatic time series, or seasonality, might aid in the prediction of average fire activity, but it is not known whether these findings are applicable globally. Here, we investigate how seasonality can be used to explain variations in fire activity on a global scale. Location Global, 60° S–60° N. Time period Data averaged over the period 1999–2015. Methods We describe a method to partition a periodic seasonal cycle into two seasons and define conceptually simple temporal metrics that describe spatial variability in seasonality. We explore the usefulness of these metrics in explaining global fire activity using the average monthly time series of precipitation and temperature and a flexible machine learning procedure (random forests). Results A simple model that uses only precipitation and temperature amplitude and synchrony between wet and warm seasons correctly predicts 66% of the variability in global fire activity, substantially more than a model with mean annual temperature and precipitation. A more complex model that includes all nine metrics predicts 87% of variability in global fire activity. Main conclusions This study shows that seasonality of temperature and precipitation can be used to predict multi‐year average fire activity in a globally relevant way. The mechanisms highlighted in our work could be used to improve global fire models and enhance their ability to represent the spatial patterns of fire activity. Our method might also be useful in hindcasting historical fire using reanalysis or predicting future fire regimes using coarse output from climate models.

A comparative study of segmentation techniques for the quantification of brain subcortical volume - Theophilus N. Akudjedu; Leila Nabulsi; Migle Makelyte; Cathy Scanlon; Sarah Hehir; Helen Casey; Srinath Ambati; Joanne Kenney; Stefani O’Donoghue; Emma McDermott; Liam Kilmartin; Peter Dockery; et al. (Brain Imaging and Behavior, 2018)

An Approach to Integrating Occupational Safety and Health into Life Cycle Assessment: Development and Application of Work Environment Characterization Factors - Kelly A. Scanlon; Shannon M. Lloyd; George M. Gray; Royce A. Francis; Peter LaPuma (Journal of Industrial Ecology, 2015)
Summary Integrating occupational safety and health (OSH) into life cycle assessment (LCA) may provide decision makers with insights and opportunities to prevent burden shifting of human health impacts between the nonwork environment and the work environment. We propose an integration approach that uses industry‐level work environment characterization factors (WE‐CFs) to convert industry activity into damage to human health attributable to the work environment, assessed as disability‐adjusted life years (DALYs). WE‐CFs are ratios of work‐related fatal and nonfatal injuries and illnesses occurring in the U.S. worker population to the amount of physical output from U.S. industries; they represent workplace hazards and exposures and are compatible with the life cycle inventory (LCI) structure common to process‐based LCA. A proof of concept demonstrates application of the WE‐CFs in an LCA of municipal solid waste landfill and incineration systems. Results from the proof of concept indicate that estimates of DALYs attributable to the work environment are comparable in magnitude to DALYs attributable to environmental emissions. Construction and infrastructure‐related work processes contributed the most to the work environment DALYs. A sensitivity analysis revealed that uncertainty in the physical output from industries had the most effect on the WE‐CFs. The results encourage implementation of WE‐CFs in future LCA studies, additional refinement of LCI processes to accurately capture industry outputs, and inclusion of infrastructure‐related processes in LCAs that evaluate OSH impacts.

A Financial and Environmental Analysis of Constructed Wetlands for Industrial Wastewater Treatment - Johnathan L. DiMuro; France M. Guertin; Rich K. Helling; Jessica L. Perkins; Scanlon Romer (Journal of Industrial Ecology, 2014)
Summary The Dow Chemical Co. (Dow) is actively working to develop an approach to value ecosystem services and incorporate them in business decisions. This study investigates the use of replacement cost methodology (RCM) for financial analysis and life cycle assessment (LCA) for environmental assessment. The case study analyzes a business decision made in 1995, where a constructed wetland was built instead of a sequencing batch reactor to solve a regulatory compliance issue in meeting suspended solids requirements for a wastewater treatment system at the Union Carbide Corp. (a subsidiary of The Dow Chemical Co.) plant in Seadrift, Texas. The financial results indicate that the total net present value savings calculated for implementing the constructed wetland instead of the sequencing batch reactor is $282 million over the project's lifetime. The LCA demonstrates that the lower energy and material inputs to the constructed wetland resulted in lower potential impacts for fossil fuel use, acidification, smog formation, and ozone depletion and likely lead to lower potential impacts for global warming and marine eutrophication. The result from the inventory of land use shows that both the upstream land burdens (for the sequencing batch reactor) and the on‐site acreage of the constructed wetland are similar in magnitude and importance, contrary to the assumption that green infrastructure always requires greater land area. This case study illustrates how Dow can consider financial and environmental analyses in comparing gray and green infrastructure solutions and further understand the benefits of implementing green infrastructure in an appropriate industrial application.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

The Dublin SURGE Project: geochemical baseline for heavy metals in topsoils and spatial correlation with historical industry in Dublin, Ireland - M. M. Glennon; P. Harris; R. T. Ottesen; R. P. Scanlon; P. J. O’Connor (Environmental Geochemistry and Health, 2014)
The Dublin SURGE (Soil Urban Geochemistry) Project is Dublin’s first baseline survey of heavy metals and persistent organic pollutants in topsoils and is part of a Europe-wide initiative to map urban geochemical baselines in ten cities. 1,058 samples were collected as part of a stratified random sampling programme in the greater Dublin area to give an overview of baseline conditions in the city. Samples were analysed for 31 inorganic elements including heavy metals. Analysis of results indicates that the concentrations of lead, copper, zinc and mercury are strongly influenced by human activities, with elevated concentrations in the city docklands, inner city and heavy industry areas. Sources of heavy metals in these areas may include historical industry, coal burning, re-use of contaminated soil, modern traffic and leaded paint and petrol. Concentrations of other inorganic elements in topsoil show patterns which are strongly related to regional bedrock parent material. The spatial distributions of heavy metals, in particular Pb and As, are explored in detail with respect to regional geology and the influence of historical industry on soil quality. Exploratory data, geostatistical and correlation analyses suggest that the concentrations of heavy metals tend to increase as the intensity of historical industrial activity increases. In particular, drinks production, power generation, oil/gas/coal, metals and textile historical industries appear to be the contamination source for several heavy metals. The data provide a geochemical baseline relevant to the protection of human health, compliance with environmental legislation, land use planning and urban regeneration.

Assessing carcass and meat characteristics of Damara, Dorper and Australian Merino lambs under restricted feeding - André M. Almeida; Tanya Kilminster; Tim Scanlon; Susana S. Araújo; John Milton; Chris Oldham; Johan C. Greeff (Tropical Animal Health and Production, 2013)

Topographical Influences on the Spatial Distribution of Soil Mercury at the Catchment Scale - Thushara Gunda; Todd M. Scanlon (Water, Air, & Soil Pollution, 2013)

Chemical Synthesis of a Fluorescent IGF-II Analogue - Jade M. Cottam; Denis B. Scanlon; John A. Karas; Antonio N. Calabrese; Tara L. Pukala; Briony E. Forbes; John C. Wallace; Andrew D. Abell (International Journal of Peptide Research and Therapeutics, 2013)

Streamwater Particulate Mercury and Suspended Sediment Dynamics in a Forested Headwater Catchment - Ami L. Riscassi; Kelly J. Hokanson; Todd M. Scanlon (Water, Air, & Soil Pollution, 2011)

Comprehensive N-Methyl Scanning of a Potent Peptide Inhibitor of Malaria Invasion into Erythrocytes Leads to Pharmacokinetic Optimization of the Molecule - Denis Scanlon; Karen S. Harris; Andrew M. Coley; John A. Karas; Joanne L. Casey; Andrew B. Hughes; Michael Foley (International Journal of Peptide Research and Therapeutics, 2008)

Estimating groundwater recharge in a cold desert environment in northern China using chloride - John B. Gates; W. M. Edmunds; Jinzhu Ma; Bridget R. Scanlon (Hydrogeology Journal, 2008)

Factors affecting river health and its assessment over broad geographic ranges: The Western Australian experience - S. A. Halse; M. D. Scanlon; J. S. Cocking; M. J. Smith; W. R. Kay (Environmental Monitoring and Assessment, 2007)

Influence of surface heterogeneity on scalar dissimilarity in the roughness sublayer - Christopher A. Williams; Todd M. Scanlon; John D. Albertson (Boundary-Layer Meteorology, 2007)

Genetic variation at the growth hormone (GH1) and growth hormone receptor (GHR) loci as a risk factor for hypertension and stroke - Martin Horan; Vicky Newsway; Yasmin; Mark D. Lewis; Tammy E. Easter; D. Aled Rees; Arti Mahto; David S. Millar; Annie M. Procter; Maurice F. Scanlon; Ian B. Wilkinson; Ian P. Hall; et al. (Human Genetics, 2006)

Application of a quartz crystal microbalance to evaluate biodegradability of starch by Bacillus subtilis - M. Jenkins; M. Horsfall; D. Mathew; M. Scanlon; R. Jayasekara; G.T. Lonergan (Biotechnology Letters, 2004)

Canopy scale measurements of CO 2 and water vapor exchange along a precipitation gradient in southern Africa - Todd M. Scanlon; John D. Albertson (Global Change Biology, 2004)
Short‐term measurements of carbon dioxide, water, and energy fluxes were collected at four locations along a mean annual precipitation gradient in southern Africa during the wet (growing) season with the purpose of determining how the observed vegetation–atmosphere exchange properties are functionally related to the long‐term climatic conditions. This research was conducted along the Kalahari Transect (KT), one in the global set of International Geosphere‐Biosphere Program transects, which covers a north–south aridity gradient, all on a homogenous sand formation. Eddy covariance instruments were deployed on a permanent tower in Mongu, Zambia (879 mm of rainfall per year), as well as on a portable tower in Maun (460 mm yr −1 ), Okwa River Crossing (407 mm yr −1 ), and Tshane (365 mm yr −1 ), Botswana for several days at each site. The relationships between CO 2 flux, F c , and photosynthetically active radiation were described well by a hyperbolic fit to the data at all locations except for Mongu, the wettest site. Here, there appeared to be an air temperature effect on F c . While daytime values of F c routinely approached or exceeded −20 μmol m −2 s −1 at Mongu, the magnitude of F c remained less than −10 μmol m −2 s −1 when the air temperature was above 27°C. Canopy resistances to water vapor transfer, r c , displayed an overall decline from the wetter sites to the more arid sites, but the differences in r c could be almost exclusively accounted for by the decrease in leaf area index (LAI) from north to south along the KT. Ecosystem water use efficiency (WUE), defined as the ratio of net carbon flux to evapotranspiration, showed a general decrease with increasing vapor pressure deficit, D , for all of the sites. The magnitudes of WUE at a given D , however, were dissimilar for the individual sites and were found to be stratified according to the position of the sites along the long‐term aridity gradient. For example, Mongu, which has the wettest climate, has a much lower WUE for like levels of D than Tshane, which historically has the most arid climate. Given the similar inferred stomatal resistances between the sites, the disparate carbon uptake behavior for the grass vs. woody vegetation is the likely cause for the observed differences in WUE along the aridity gradient. The short‐term flux measurements provide a framework for evaluating the vegetation's functional adaptation to the long‐term climate and provide information that may be useful for predicting the dynamic response of the vegetation to future climate change.

Self-Micellization of Gemfibrozil 1-O-β Acyl Glucuronide in Aqueous Solution - David M. Shackleford; Richard J. Prankerd; Martin J. Scanlon; William N. Charman (Pharmaceutical Research, 2003)

Effect of storage period, cultivar and two growing locations on the processing quality of french fried potatoes - A. Agblor; M. G. Scanlon (American Journal of Potato Research, 2002)

Processing conditions influencing the physical properties of French fried potatoes - A. Agblor; M. G. Scanlon (Potato Research, 2000)

Effects of blanching conditions on the mechanical properties of french fry strips - A. Agblor; M. G. Scanlon (American Journal of Potato Research, 1998)

Phenotypic analysis and molecular cloning of discolored-1 (dsc1), a maize gene required for early kernel development - Michael J. Scanlon; Alan M. Myers (Plant Molecular Biology, 1998)

Computerized video image analysis to quantify color of potato chips - M. G. Scanlon; R. Roller; G. Mazza; M. K. Pritchard (American Journal of Potato Research, 1994)